Mortality outcomes of ruptured abdominal aortic aneurysms and rural presentation. (October 2016) - Munday, Emily; Walker, Stuart
Objectives: Centralisation of vascular surgery services has coincided with a move towards endovascular repair of ruptured abdominal aortic aneurysms with the goal to improve patient outcomes. The aim of this study was to assess the effect of rural presentation and transfer times on survival from ruptured abdominal aortic aneurysm. Design: A retrospective review. Materials: All patients presenting with ruptured abdominal aortic aneurysm to public hospitals in Tasmania between July 2006 and April 2013. Methods: Demographic data, Glasgow aneurysm score, Hardman index, transfer times, operative technique and 30-day mortality were collected from medical records. Results: Over the study period 127 patients presented to public hospitals in Tasmania with ruptured abdominal aortic aneurysm. A total of 27 presented to north west hospitals where no vascular surgery service is provided (NWRH), 23 to a northern hospital where an intermittent vascular surgery service is provided (LGH) and 77 to the state tertiary vascular surgery service (RHH). Of these, 4 (14.8%) died at NWRH, 6 (26.1%) died at LGH and 43 (55.8%) died at RHH without operation. Of the 35 patients transferred from NWRH and LGH to RHH, 5 died without operation. Median time from presentation to theatre at RHH if transferred from NWRH was 6.25 hours, from the LGH 4.75 hours, compared to 2.75 hours when presenting directly to RHH. Open repair was performed in 41 patients and endovascular repair in 23 patients. Overall 30-day mortality in those treated at RHH was 26.6% (39.0% for open repair, 4.3% for endovascular repair). Mortality for intended operative patients initially presenting to non-RHH hospitals was 33.3% vs. 32.3% for those initially presenting to RHH. p Value 0.93. Conclusion: There was no clinical or statistical disadvantage to rural presentation and transfer for patients presenting with ruptured abdominal aortic aneurysm in Tasmania. Endovascular repair has a role despite long transfer times.